Olympus: When the gods came tumbling down - OHLSSON-CORBOZ, Anne-Valerie (Institutional Knowledge at Singapore Management University, 2014)
In April 2011, Michael Woodford, a British national, was appointed President and Chief Operating Officer of Olympus. Within months of becoming President, Woodford discovered that Olympus had made some questionable acquisitions and paid large amounts of money for companies with few assets, and exorbitant advisory fees to non-substantive companies based in the Cayman Islands. It became clear to him that colleagues and respected Board members within the company had propagated and concealed this fraud. Woodford was distressed by the fact that these fraudulent dealings had cost Olympus shareholders more than a billion dollars. When Woodford confronted the Olympus Chairman, Tsuyoshi Kikukawa, and other executives, demanding the truth, he was met by silence or given ambiguous answers. Woodford believed the only way to clear up the mess before it spiralled out of control was for the company to face the allegations, appoint him CEO and have the Chairman and existing Board resign. Initially, it appeared that the company was supportive, and he was promoted to the role of CEO on October 1, 2011. However, Woodford then realised that the board was not aligned with him and would resist providing any transparency about the allegations. He made a decision to hire PriceWaterhouseCoopers (PwC) for an independent audit and analysis of the transactions. PwC produced a disturbing report that made clear the acquisitions and the related payments were suspect and required further investigation. On October 13, 2011, Woodford sent PwC’s report to Kikukawa, suggesting that he resign as the honourable way to face this scandal. He also proactively sent copies of each letter to Olympus’s external auditors at Ernst & Young, knowing this would force the issue out into the open. He hoped that a Board meeting on October 14 would trigger the action needed for Olympus to begin its recovery and gain transparency. What he had not anticipated was that at this meeting he would be terminated from his position, relieved of his board seat, told to turn in his mobile phone, laptop and all related business items and to “take a bus” to the airport. The material covered in this case allows for several topics to be discussed relating to crisis management: whistleblowing, corporate governance, accounting scandals, leadership, cultural values, ethics and shareholder value and obligation. Depending on the facilitator’s interest and intent, the learning objectives can also be adapted to include related topics like corporate scandals, the emergence of corporate governance reform, Sarbanes-Oxley legislation, the UK Bribery Act, and discuss the decision of many public companies to put in place two-tiered boards so that shareholders have oversight on management.